Endogenous innovation and digital inclusion: A Global African perspective - Soumonni, Ogundiran; Monroe-White, Thema (University of the Witwatersrand, Johannesburg, 2023)
This paper systematically reflects on the myriad ways in which Africans, understood as a global people who include their Diaspora, can more effectively draw on their own technological capabilities in order to achieve more inclusive and equitable digital outcomes. We begin with the observation that while ongoing scholarly and policy discourses on the global digital revolution optimistically highlight its opportunities for African societies, the imperative of the domestic contribution to these – endogenous innovation – is often buried among numerous other considerations. As such, our study delineates the diverse, though mutually reinforcing, ways in which endogenous technological innovation, ranging from research and development (R&D) to the novel deployment of existing technologies, is effectively employed by intentional actors in state, private sector and grassroots organisations. Digital governance in this perspective is then informed by constant attention to the interplay between these two dimensions (governance and technological innovation) with the ultimate aim of achieving universal and equitable digital access, particularly in less privileged Global African societies, and within a relatively short time horizon. Lastly, informed by historical path dependence, that is, philosophical, technical and experiential examples from the past, we develop a conceptual framework which we call endogenous digital innovation. This framework more explicitly highlights some of the critical pathways that could lead to desirable socio-technical futures in the African world.
Keywords: African Governance; Digital Age; Digital inclusion; Endogenous innovation; Innovation; SDG-9: Industry, innovation and infrastructure